Multifunctional Mo–N/C@MoS2 Electrocatalysts for HER, OER, ORR, and Zn–Air Batteries. (29th September 2017) - Amiinu, Ibrahim Saana; Pu, Zonghua; Liu, Xiaobo; Owusu, Kwadwo Asare; Monestel, Hellen Gabriela Rivera; Boakye, Felix Ofori; Zhang, Haining; Mu, Shichun
Abstract: Replacement of noble‐metal platinum catalysts with cheaper, operationally stable, and highly efficient electrocatalysts holds huge potential for large‐scale implementation of clean energy devices. Metal–organic frameworks (MOFs) and metal dichalcogenides (MDs) offer rich platforms for design of highly active electrocatalysts owing to their flexibility, ultrahigh surface area, hierarchical pore structures, and high catalytic activity. Herein, an advanced electrocatalyst based on a vertically aligned MoS2 nanosheet encapsulated Mo–N/C framework with interfacial Mo–N coupling centers is reported. The hybrid structure exhibits robust multifunctional electrocatalytic activity and stability toward the hydrogen evolution reaction, oxygen evolution reaction, and oxygen reduction reaction. Interestingly, it further displays high‐performance of Zn–air batteries as a cathode electrocatalyst with a high power density of ≈196.4 mW cm −2 and a voltaic efficiency of ≈63 % at 5 mA cm −2, as well as excellent cycling stability even after 48 h at 25 mA cm −2 . Such outstanding electrocatalytic properties stem from the synergistic effect of the distinct chemical composition, the unique three‐phase active sites, and the hierarchical pore framework for fast mass transport. This work is expected to inspire the design of advanced and performance‐oriented MOF/MD hybrid‐based electrocatalysts for wider application in electrochemical energy devices. Abstract : An advanced electrocatalyst is designed based on a vertically‐aligned MoS2 nanosheet encapsulated Mo–N/C framework with Mo–N coupling centers at the interface. The hybrid electrocatalyst exhibits high multifunctional activity and stability toward the hydrogen evolution reaction, oxygen evolution reaction, and oxygen reduction reaction, as well as high Zn–air battery performance.